Effects of Nitrogen Deposition on Typical Hydrolytic Enzyme Activities by Fluorimetric Assay - Zhang1, G.N.; Chen1, Z.H.; Zhang1, A.M.; Chen1, L.J.; Wu4, Z.J. (Asian Journal of Chemistry, 2013)
Soil properties and five hydrolytic enzyme activities under different simulated nitrogen deposition treatments were determined under semi-arid grassland in Northern China. Significant acidification was observed under N addition treatments. Highest values of soil total carbon, phosphorus and olsen-P concentration was observed in medium level of N application. Soil acid phosphomonoesterase, phosphodiesterase and N-acetyl-b-D-glucosaminidase activities increased with N amendment. The b-D-glucosidase and arylsulfatase activities were stimulated under medium level of N addition. The principal components analysis showed that N deposition might influence soil enzyme activities indirectly through soil pH, total carbon, total phosphorus and olsen-P concentration. Furthermore, the principal component analysis also showed similarity of N2.8 and N4.0 treatments, which indicated N saturation at 2.8 mol N m-2 yr-1 in the study area.